Construction of protein expression vector to consist metroxylon sagu chitinase cDNA - Yong, Elise Yih Lih. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Chitinase cDNA is a gene that involves in plant response against pathogens and has been isolated from the sago palm, Metroxylon sagu. In this study, E.coli XLI Blue competent cells was prepared and the pUC191msChi and pET41a+ plasmids were transformed into the competent cells. Colonies grown in Luria Bertani agar plates were picked up and cultured in Luria Bertani broth on the next day. The plasmids were extracted and the presence of chitinase cDNA in pUC191msChi plasmid was verified through polymerase chain reaction (PCR). The formed PCR products were then purified by using silica bead DNA gel extraction kit. pET41a+ plasmid was cut with XbaI restriction enzyme, followed by bluntending pET41a+ plasmid and the PCR products with T4 DNA polymerase and cut with HindllI enzyme. However, restriction analysis ofpET41a+ plasmid was not successful. For future study, it is suggested that the condition of the restriction enzyme reaction is needed to be optimized.